Assessing and evaluating preschoolers' socio-emotional skills - Bernhauser, Lara-Elain (2016)
Identifying emotions is an important skill for everyone. As skills like others, socio– emotional skills have to be learned and improved while ageing. This thesis focused on preschoolers' socio-emotional competence and how these skills appear when assessed by the children themselves versus evaluation done by caregivers, who are represented by preschool teachers and parents. The socio-emotional skills of 23 children were evaluated and assessed in three different ways, both by the children themselves (Assessment of Children’s Emotions Scales ACES) and The diagnostic analysis of non-verbal accuracy 2 (DANVA 2) and by the teachers and parents (Behavioral and Emotional Rating Scale, Pre - BERS) for each child.